Targeting DNA methylation can reduce cardiac injury associated with ischemia reperfusion: One step closer to clinical translation with blood-borne assessment - Boovarahan, Sri Rahavi; AlAsmari, Abdullah F.; Ali, Nemat; Khan, Rehan; Kurian, Gino A. (Frontiers in Cardiovascular Medicine, 2022)
Ischemia reperfusion injury (I/R) is one of the main clinical challenges for cardiac surgeons. No effective strategies or therapy targeting the molecular and cellular mechanisms to reduce I/R exists to date, despite altered gene expression and cellular metabolism/physiology. We aimed to identify whether DNA methylation, an unexplored target, can be a potential site to curb I/R-associated cell death by using the left anterior descending artery occlusion model in male Wistar rats. I/R rat heart exhibited global DNA hypermethylation with a corresponding decline in the mitochondrial genes (PGC-1α, TFAM, POLG, ND1, ND3, ND4, Cyt B, COX1 and COX2), antioxidant genes (SOD2, catalase, Gpx2) and elevation in apoptotic genes (Casp3, Casp 7, Casp9) expression with corresponding changes in their activity, resulting in injury. Targeting global DNA methylation in I/R hearts by using its inhibitor significantly reduced the I/R-associated infarct size by 45% and improved dysferlin levels via modulating the genes involved in cell death apoptotic pathway (Casp3, Casp7 and PARP), inflammation (IL-1β, TLR4, ICAM1, MyD88), oxidative stress (SOD1, catalase, Gpx2, NFkB) and mitochondrial function and its regulation (MT-ND1, ND3, COX1, ATP6, PGC1α, TFAM) in the cardiac tissue. The corresponding improvement in the genes' function was reflected in the respective hearts via the reduction in apoptotic TUNEL positive cells and ROS levels, thereby improving myocardial architecture (H&E staining), antioxidant enzymes (SOD, catalase activity) and mitochondrial electron transport chain activities and ATP levels. The analysis of blood from the I/R animals in the presence and absence of methylation inhibition exhibited a similar pattern of changes as that observed in the cardiac tissue with respect to global DNA methylation level and its enzymes (DNMT and TET) gene expression, where the blood cardiac injury markers enzymes like LDH and CK-MB were elevated along with declined tissue levels. Based on these observations, we concluded that targeting DNA methylation to reduce the level of DNA hypermethylation can be a promising approach in ameliorating I/R injury. Additionally, the blood-borne changes reflected I/R-associated myocardial tissue alteration, making it suitable to predict I/R-linked pathology.